Produktivity of Indigofera zollingeriana Plants which were Given Several Types and Doses of Rice Washing Water - J. O., Sena,; Witariadi, N. M.; Roni, N G. K. (Jurnal Peternakan Tropika; Vol 7 No 3 (2019): Issue 7 No. 3 - 2019; September - December 2019, 2019)
This study aims to determine the productivity of Indigofera zollingeriana plants which are given the type and dose of rice water.  This research was conducted at the Greenhouse of the Faculty of Animal Husbandry Research Station of Udayana University, Highway Sesetan Markisa up to 3 months.  The design used is a completely randomized design (RAL) factorial with 2 factors.  The first factor is rice water types consist of C?: fresh rice washing water and C?: fermented rice water, while the second factor is the dose of rice water consist of D?: without rice water/control, D?: 50 kg N/ha, D?: 100 kg N/ha, D?: 150 kg N/ha, D?: 200 kg N/ha, D?: 250 kg N/ha.  From the design, 12 treatment combinations were obtained and each treatment combination was repeated 3 times to obtain 36 experimental units.  Variables observed were plant height, number of leaves, number of nodules, number of branches, leaf dry weight, stem dry weight, root dry weight, forage total dry weight, leaf area, leaf dry weight ratio with stem dry weight and weight ratio total dry forage with root dry weight.  The results showed that the factor of rice washing water statistically sigficantly affected the variable height of plants, number of leaves, leaf dry weight, stem dry weight, root dry weight, total dry weight of forgae and leaf area, while the dose factor for rice washing water has a statistically significant effect on the number of leaves, number of branches, dry weight of leaves and leaf area.  Based on the results of this study concluded that the productivity of Indigofera zollingeriana plants which were given fresh rice washing water was better that fermented rice washing water.  An Increase in the dose of rice washing water decreases the productivity of Indigofera zollingeriana plants. At dosage D? gives the best results except for the number of root nodules, the ratio of leaf dry weight to stem dry weight and the ratio of total dry weight to forage with root dry weight.  An interaction between the type and dose of rice washing water on variable plant height, leaf dry weight and leaf area.   Keywords: productivity, Indigofera zollingeriana, rice washing wat